Signatures of fractional quantum anomalous Hall states in twisted MoTe2 - Cai, Jiaqi; Anderson, Eric; Wang, Chong; Zhang, Xiaowei; Liu, Xiaoyu; Holtzmann, William; Zhang, Yinong; Fan, Fengren; Taniguchi, Takashi; Watanabe, Kenji; Ran, Ying; Cao, Ting; et al. (Nature, 2023)
The interplay between spontaneous symmetry breaking and topology can result in exotic quantum states of matter. A celebrated example is the quantum anomalous Hall (QAH) state, which exhibits an integer quantum Hall effect at zero magnetic field owing to intrinsic ferromagnetism 1 – 3 . In the presence of strong electron–electron interactions, fractional QAH (FQAH) states at zero magnetic field can emerge 4 – 8 . These states could host fractional excitations, including non-Abelian anyons—crucial building blocks for topological quantum computation 9 . Here we report experimental signatures of FQAH states in a twisted molybdenum ditelluride (MoTe 2 ) bilayer. Magnetic circular dichroism measurements reveal robust ferromagnetic states at fractionally hole-filled moiré minibands. Using trion photoluminescence as a sensor 10 , we obtain a Landau fan diagram showing linear shifts in carrier densities corresponding to filling factor v = −2/3 and v = −3/5 ferromagnetic states with applied magnetic field. These shifts match the Streda formula dispersion of FQAH states with fractionally quantized Hall conductance of σ x y = − 2 3 e 2 h and σ x y = − 3 5 e 2 h , respectively. Moreover, the v = −1 state exhibits a dispersion corresponding to Chern number −1, consistent with the predicted QAH state 11 – 14 . In comparison, several non-ferromagnetic states on the electron-doping side do not disperse, that is, they are trivial correlated insulators. The observed topological states can be electrically driven into topologically trivial states. Our findings provide evidence of the long-sought FQAH states, demonstrating MoTe 2 moiré superlattices as a platform for exploring fractional excitations. Signatures of fractional quantum anomalous Hall states at zero magnetic field are observed in a fractionally filled moiré superlattice in a molybdenum ditelluride twisted bilayer.